Therapeutic Advances In Rheumatoid Arthritis: A Comprehensive Review On The Role Of Dmards And Biologic Agents - Angel.S, Jacintha Abisha; Amargeeth, Surendhar; Kuamri, Hepsiba Selva; Keerthiga, Keerthiga; Shathika, Shathika; Hensha, Hensha; Krishnan, Karthickeyan (Journal of Neonatal Surgery, 2025)
Background: Rheumatoid arthritis (RA) is a long-lasting autoimmune inflammatory disease that causes gradual joint damage, pain, and disability. In recent years, treatment methods have shifted from simply managing symptoms to using targeted immune therapies with disease-modifying antirheumatic drugs (DMARDs) and biologics. Objective: This review aims to evaluate recent advancements in RA treatment, focusing on conventional synthetic disease-modifying antirheumatic drugs (csDMARDs), targeted synthetic disease-modifying antirheumatic drugs (tsDMARDs), and biologic disease-modifying antirheumatic drugs (bDMARDs). It will highlight their mechanisms, effectiveness, and safety. Methods: A narrative literature review was conducted by searching PubMed, Scopus, and Google Scholar for articles published between 2000 and 2024. The keywords used were “Rheumatoid Arthritis,” “DMARDs,” “biologics,” and “JAK inhibitors.” We prioritized randomized controlled trials, meta-analyses, and clinical guidelines from EULAR and ACR. Results: Methotrexate is still the mainstay of csDMARD therapy and effectively controls disease activity. JAK inhibitors like tofacitinib and baricitinib offer effective oral options with quick symptom relief. Biologic agents, including TNF inhibitors and non-TNF biologics (tocilizumab, rituximab), have improved outcomes for patients with hard-to-treat RA. Using combinations and starting aggressive therapies early increases remission rates. Safety issues, such as the risk of infection, liver toxicity, and heart events, require careful monitoring of patients. Conclusion: Recent advances in DMARDs and biologics have changed how RA is managed, allowing for targeted and personalized treatments. A strategy focused on treating to target, which includes early intervention and the involvement of clinical pharmacists, is crucial for achieving optimal outcomes. Future developments in biosimilars and therapies guided by biomarkers promise even more improvements